Doświadczenie religijne w życiu codziennym młodzieży polskiej w XXI wieku - Mariański, Janusz (Humaniora. Czasopismo Internetowe, 2022)
In these sociological analyzes we will pay attention to selected aspects of religious experience in the consciousness of Polish youth. On one hand, these will be the contents of a religious experience, that is, everything that a person experiences in his relation to God and that gives him grounds for believing; on the other hand, to approximate the function of religious experience in shaping attitudes towards faith and living it every day. In the light of the results of sociological research carried out in youth circles, we analyze three issues: the experience of God’s presence in the consciousness of young people, religious experience in everyday life, religious faith and a sense of security. If we characterize a person’s religiosity from the point of view of believing in a personal God whom a person wants to trust and expects help from, the examined youth turned out to be moderately religious. Various manifestations of religious experience were emphasized more often by women than by men, college students more often than secondary school students, youth living in the countryside more often than those living in the city, having parents with primary education more often than with higher education.